2015
DOI: 10.1080/10916466.2014.948120
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Operating Temperatures on Wax Deposition During Cold Flow and Hot Flow of Crude Oil

Abstract: The authors examined the effect of operating temperatures on the wax deposition by using the cold finger device and high-temperature gas chromatography. The decreases in coolant temperature have been observed to result in increases in the amount of total deposit, but decreases in the amount of high carbon number components in deposit. When the bulk oil temperature increases from the gelling, cold flow, and hot flow conditions, the deposition rate decreases first, then increases, and then finally decreases whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Because of the waxy nature of TOs, the deposition of wax can cause equipment malfunctioning during transportation by both pipeline and railway as well as prolonged storage of TOs. , The study by Ding et al showed that information on the rheological properties of TOs (e.g., viscosity, gel point, yield stress, and thixotropy) is needed for monitoring the operation of pipelines transporting TOs. Thus, a rather complex wax deposition pattern with increasing temperature were reported by Quan et al For example, when the temperature of waxy oil was increased from gelling, to cold flow, to hot flow conditions, the wax deposition rate decreased, then increased, and again decreased. These problems may be alleviated by the addition of flow improvers…”
Section: Properties Of Tight Oilsmentioning
confidence: 80%
“…Because of the waxy nature of TOs, the deposition of wax can cause equipment malfunctioning during transportation by both pipeline and railway as well as prolonged storage of TOs. , The study by Ding et al showed that information on the rheological properties of TOs (e.g., viscosity, gel point, yield stress, and thixotropy) is needed for monitoring the operation of pipelines transporting TOs. Thus, a rather complex wax deposition pattern with increasing temperature were reported by Quan et al For example, when the temperature of waxy oil was increased from gelling, to cold flow, to hot flow conditions, the wax deposition rate decreased, then increased, and again decreased. These problems may be alleviated by the addition of flow improvers…”
Section: Properties Of Tight Oilsmentioning
confidence: 80%
“…*Formation and deposition of paraffin wax on the inner wall of production facilities and transportation pipelines continues to be a critical operational problem faced by the oil industry (Alcazar-Vara and Buenrostro-Gonzalez, 2013; Jafari Ansaroudi et al, 2013;Chala et al, 2014;Coto et al, 2014;Elhaddad et al, 2015;Zhang, 2014;Quan et al, 2015). Petroleum industries worldwide have been threatened by the risk of wax crystallisation and deposition which leads to tremendous economic losses due to the chemicals, well shut-in, choking of the flowlines, reduced production, less utilization of capacity, increased manpower attention and extra horse-power requirement.…”
Section: Introductionmentioning
confidence: 99%